Absence of myoepithelial cells correlates with invasion and metastasis of Carcinoma ex pleomorphic adenoma. Issue 8 (August 2017) - Ye, P.; Gao, Y.; Wei, T.; Yu, G.-Y.; Peng, X.
Abstract: Myoepithelial cells (MECs) are implicated in the development and progression of human salivary gland tumours. Here, we investigate the potential role for MECs in invasion and metastasis of carcinoma ex pleomorphic adenoma (CXPA). Tumour tissues from 40 CXPA patients diagnosed between 1960 and 2014 were obtained. Patient samples were divided into two groups (non-invasive tumours, n = 10; and frankly invasive tumours, n = 30). Each group was further divided into two subgroups (metastatic tumours and non-metastatic tumours). Immunohistochemistry for MEC markers (α-SMA, CALPONIN, and p63) was performed, and the number and distribution of MECs was quantified. For non-invasive CXPAs, non-metastatic cases ( n = 8) displayed a significant enrichment in CALPONIN(+) and α-SMA(+) MECs, but not p63(+) MECs, compared with metastatic cases ( n = 2). Likewise, for frankly invasive CXPAs ( n = 30), non-metastatic cases showed a significant enrichment for α-SMA(+), CALPONIN(+), and p63(+) MECs compared with metastatic cases ( n = 15). We demonstrate that non-invasive CXPAs have the potential for metastasis. Furthermore, the tumour capsule may not be the only barrier preventing invasion and metastasis, as a significant reduction in numbers of myoepithelial cells correlates with invasion and metastasis in CXPA patients.